Readability Analysis of the Package Leaflets for Biological Medicines Available on the Internet Between 2007 and 2013: An Analytical Longitudinal Study - Piñero-López, María Ángeles (J Med Internet Res, 2016)
BACKGROUND: The package leaflet included in the packaging of all medicinal products plays an important role in the transmission of medicine-related information to patients. Therefore, in 2009, the European Commission published readability guidelines to try to ensure that the information contained in the package leaflet is understood by patients. OBJECTIVE: The main objective of this study was to calculate and compare the readability levels and length (number of words) of the package leaflets for biological medicines in 2007, 2010, and 2013. METHODS: The sample of this study included 36 biological medicine package leaflets that were downloaded from the European Medicines Agency website in three different years: 2007, 2010, and 2013. The readability of the selected package leaflets was obtained using the following readability formulas: SMOG grade, Flesch-Kincaid grade level, and Szigriszt’s perspicuity index. The length (number of words) of the package leaflets was also measured. Afterwards, the relationship between these quantitative variables (three readability indexes and length) and categorical (or qualitative) variables were analyzed. The categorical variables were the year when the package leaflet was downloaded, the package leaflet section, type of medicine, year of authorization of biological medicine, and marketing authorization holder. RESULTS: The readability values of all the package leaflets exceeded the sixth-grade reading level, which is the recommended value for health-related written materials. No statistically significant differences were found between the three years of study in the readability indexes, although differences were observed in the case of the length (P=.002), which increased over the study period. When the relationship between readability indexes and length and the other variables was analyzed, statistically significant differences were found between package leaflet sections (P<.001) and between the groups of medicine only with regard to the length over the three studied years (P=.002 in 2007, P=.007 in 2010, P=.009 in 2013). Linear correlation was observed between the readability indexes (SMOG grade and Flesch-Kincaid grade level: r(2)=.92; SMOG grade and Szigriszt’s perspicuity index: r(2)=.81; Flesch-Kincaid grade level and Szigriszt’s perspicuity index: r(2)=.95), but not between the readability indexes and the length (length and SMOG grade: r(2)=.05; length and Flesch-Kincaid grade level: r(2)=.03; length and Szigriszt’s perspicuity index: r(2)=.02). CONCLUSIONS: There was no improvement in the readability of the package leaflets studied between 2007 and 2013 despite the European Commission’s 2009 guideline on the readability of package leaflets. The results obtained from the different readability formulas coincided from a qualitative point of view. Efforts to improve the readability of package leaflets for biological medicines are required to promote the understandability and accessibility of this online health information by patients and thereby contribute to the appropriate use of medicines and medicine safety.